Study on the antiemetic property of methanolic stem extract of Swertia chirata using chick emesis model - Medhi, Pranjal Kr.; Gohain, Kalpana (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Swertia chirata has been an important herb known for centuries for its various medicinal uses and bitter taste. The stem of the plant is used as a traditional medicine in an array of diseases including the treatment of vomiting. Therefore, the study was undertaken to explore the possible antiemetic property of methanolic extract of its stems by using chick emesis model. Methods: 25 male chicks of four days old weighing 25 to 35 grams were fed with copper sulfate anhydride at 50mg/kg body weight to induce emesis. The chicks were grouped into 5 with each group bearing 5 chicks (n=5). Group I (control) received 10ml/kg normal saline; group II (standard) received 150mg/kg chlorpromazine; group III (experimental-1), group IV (experimental-2) and group V (experimental-3) received 50, 100 and 150mg/kg respectively of the extract. All doses are given intraperitoneally. Assessment of antiemetic activity was done by calculating the percentage of inhibition of the number of retches in the chicks. Results: All the three doses of the extract showed antiemetic activity. The dose of 50 mg/kg showed activity comparable to chlorpromazine, while dose of 100 mg/kg and 150mg/kg showed greater activity than chlorpromazine. Highest antiemetic activity (79.26% inhibition) was shown by a dose of 150mg/kg and lowest (42.22% inhibition) by 50mg/kg. Conclusions: Methanolic extract from the stems of Swertia chirata has excellent anti-emetic property which can be further investigated for development of potential antiemetic medicines.